Comparative Study of Phytochemical and Phytomineral Analysis of Selected Peel Powders - Gana Manjusha Kondepudi (Journal of Global Pharma Technology, 2018)
ABSTRACTObjectives: The present study was conducted to evaluate the presence of phytochemicals and mineral elements composition of selected peel powders of Annona sqaumosa, Actinidia deliciosa, Cucumis melo and Mallus pumila. Methods: The phytochemical screening was conducted for the presence of alkaloids, glycosides, phenolics, carbohydrates, aminoacids, saponins, tannins, terpenoids and phytosterols in the selected peel powders. Among all the phytochemicals, phenolics were common in all selected peel powders. The mineral analysis was conducted for both trace elements (Copper, Zinc, Iron, Manganese and Potassium) and toxic elements (Cadmium and Lead). Results: The results of the study indicated that all the selected peel powders showed notable trace elements and negligible amount of toxic elements. Conclusion: Based on the results it was concluded that the fruit peels are no more waste but excellent source of phytoconstituents  and minerals. Hence they can be used in the treatment of many diseases.